Dynamics of the fecal microbiome and antimicrobial resistome in commercial piglets during the weaning period - Suriyaphol, Prapat (2021)
This study aimed to characterize the alteration of the fecal microbiome and antimicrobial resistance (AMR) determinants in 24 piglets at day 3 pre-weaning (D. - 3), weaning day (D.0), days 3 (D.3) and 8 post-weaning (D.8), using whole-genome shotgun sequencing. Distinct clusters of microbiomes and AMR determinants were observed at D.8 when Prevotella (20.9%) was the major genus, whereas at D. - 3-D.3, Alistipes (6.9-12.7%) and Bacteroides (5.2-8.5%) were the major genera. Lactobacillus and Escherichia were notably observed at D. - 3 (1.2%) and D. - 3-D.3 (0.2-0.4%), respectively. For AMR, a distinct cluster of AMR determinants was observed at D.8, mainly conferring resistance to macrolide-lincosamide-streptogramin (mefA), β-lactam (cfxA6 and aci1) and phenicol (rlmN). In contrast, at D. - 3-D.3, a high abundance of determinants with aminoglycoside (AMG) (sat, aac(6')-aph(2''), aadA and acrF), β-lactam (fus-1, cepA and mrdA), multidrug resistance (MDR) (gadW, mdtE, emrA, evgS, tolC and mdtB), phenicol (catB4 and cmlA4), and sulfonamide patterns (sul3) was observed. Canonical correlation analysis (CCA) plot associated Escherichia coli with aac(6')-aph(2''), emrA, mdtB, catB4 and cmlA4 at D. - 3, D.0 and/or D.3 whereas at D.8 associations between Prevotella and mefA, cfxA6 and aci1 were identified. The weaning age and diet factor played an important role in the microbial community composition.